O mapeamento de monóxido de carbono (CO), umidade e temperatura na cidade de Araguaína - Silva, Hevellyn Tays Lima da (Universidade Federal do Tocantins, 2020)
We aim to mathematically understand the data collected by an IoT device in order to understand which region of Araguaina has the best air quality. The internet of things goes beyond connecting devices through the internet, it enables the interaction of virtual and non-virtual things, making it possible from then on to make a decision about what is being observed. Today projects are already being created focused on environmental issues that make it possible to understand, in the case of climate effects on the atmosphere, and prevention, as in environmental disasters. Our device was built from the integration of the NodeMCU esp8266 board and the MQ-7 and DHT11 sensors, in which it collects and sends data to the Ubidots platform server, enabling real-time data visualization. He collected data of the following variables: CO, Humidity and Temperature, seeking to understand how the process of variation of these occurs, was collected data of 18 days in different sectors of the city, for the analysis we used a statistical approach of the variables. Thus, we analyze different statistical patterns, and with this our research, although not having a broader scope, because it does not contemplate many days it shows the possibility of using the internet of things to monitor environmental issues, working with various mathematical tools, both in the construction as in the analysis.